Metagenomic nanopore sequencing of ocular microbiome in patients with meibomian gland dysfunction - Jing, Dalan; Jiang, Xiaodan; Ren, Xiaotong; Su, Jie; Huang, Chen; Yang, Jiarui; Hao, Ran; Li, Xuemin (Frontiers in Medicine, 2022)
Purpose To explore the composition of the ocular microbiome in patients with Meibomian gland dysfunction (MGD) using metagenomic nanopore sequencing. Methods A total of 98 participants were recruited from September to December 2021, including 86 patients with MGD and 12 controls. Symptoms and signs of dry eye were assessed, and bacterial samples in the conjunctival sac (CS) and meibomian gland (MG) secretions were then identified by bacterial culture identification and metagenomic nanopore sequencing. Results The positive rate of CS bacterial culture in the MGD group was significantly higher than that in the normal group. A more complex composition of bacterial genera was detected in the mild and moderate MGD groups than in the control. However, the severe MGD groups had the simplest composition of bacteria. Metagenomic nanopore sequencing detected more species of bacteria than traditional culture. Conclusion The CS and MG of MGD patients may have different degrees of bacterial microbiota imbalance. Metagenomic nanopore sequencing technology provides a new way for us to understand the composition of “real-world” ocular surface microorganisms.